Pelaksanaan Kebijakan Pulang Kampung Melalui Program Petani Kopi Untuk Pemberdayaan Masyarakat Kabupaten Paniai - Sepo Nawipa; Rima Nusantriani Banurea; Fitrine Christiane Abidjulu (PT FORMOSA CENDEKIA GLOBAL, 2022)
The pattern of people moving from villages to cities has become a pattern in various places, including in Paniai Regency. This pattern makes the village 'abandoned', while the city becomes congested. Therefore, the Paniai Regency Government issued a Return to Kampung policy so that the Paniai community returned and built a village. This policy has a derivative program for Coffee Farmers, all of which are funded by the Regency government. Therefore, this study looks at the implementation of these policies from the government's perspective. This study used qualitative research methods. The data was taken using the Literature Study Technique sourced from the news media that wrote about this activity, the Paniai district government website and social media channels. The result of this research is that the coffee planting program is able to make the Paniai community return to their village and empower the Paniai community